Validation of the spanish version of the pediatric asthma caregiver quality of life questionnaire (PACQLQ) in a population of Hispanic children (2015)
Objective: The Paediatric Asthma Caregiver's Quality of Life Questionnaire (PACQLQ) is intended to measure the impact of children's asthma on their parents/caregiver's QoL. However, there are no formal validation studies of the Spanish version of PACQLQ.Methods: In a prospective cohort validation study, asthmatic children aged between 7 and 17 years and their parents, attended both a baseline and a follow-up visit 2–6 weeks later. In these two visits, we gathered the necessary data for assessing the criterion validity, construct validity, test–retest reliability, sensitivity to change, internal consistency and usability of the PACQLQ.Results: At baseline, PACQLQ scores were significantly different between patients with controlled, partly controlled and uncontrolled asthma (median [IQR] 78.0 [61.0–85.0], 71.0 [37.0–76.0] and 48.0 [40.7–55.0], respectively,p < 0.001), and also between patients for whom this visit resulted in a step-up versus no change or a step-down in therapy (50.0 [40.0–60.0] versus 78.0 [61.0–85.0];p < 0.001). PACQLQ scores at baseline were significantly lower than those obtained in the follow-up visit in patients with change for the better in the global rating of change questionnaire (median [IQR] 50.0 [42.5–56.0] versus 80.0 [78.5–85.0];p < 0.001). The intraclass correlation coefficient of the measurements was 0.839 (95%CI: 0.735–0.902). The Cronbach α was 0.914 for the questionnaire as a whole.Conclusions: The Spanish version of the PACQLQ has adequate construct validity, adequate sensitivity to change, good internal consistency, excellent test–retest reliability and good usability when employed in children aged between 7 and 17 years with physician-diagnosed asthma